The impact of emotion regulation strategies on disordered eating behavior in children and adolescents with type 1 diabetes: a cross-sectional study - Yang, Xin; Jiang, Hui; Lin, Meng; Yu, Shuang; Wu, Jin (Frontiers in Pediatrics, 2024)
Objective: Difficulties in emotion regulation (DERs) can contribute to disordered eating behavior in children and adolescents with type 1 diabetes (T1D), although it is unknown how DERs may affect eating behavior in these children and adolescents. This study examined the relationship between disordered eating behaviors and emotion regulation in children and adolescents with T1D.Methods: For this cross-sectional study, 128 patients (aged 8 -16 years) were recruited to complete the Diabetes Eating Problem Survey-Revised (DEPS-R) and Difficulties in Emotion Regulation Scale (DERs).The mean age of the 128 patients (99 females) who completed the DEPS-R was 11.63 ± 2.27 years. The participants' mean DEPS-R score was 17.78 ± 8.56 points. Of the total sample, 61 participants' scores surpassed the established threshold, resulting in a DEPS-R positivity rate of 47.66%. The participants' mean total DERS score was 72.3 ± 21.15 points, and it was found that children and adolescents with T1D who had a positive DEPS-R screening result had significant differences in emotional regulation and that eating behavior disorders were positively correlated with emotional regulation and all dimensions scores.The prevalence of disordered eating behavior is high among children and adolescents with T1D. DERs are related to disordered eating behavior in children and adolescents with T1D. The novel finding that DERs may be a predictor of eating problems lends preliminary support for the inclusion of DERs in future risk models and as a potential target for intervention.